Decreased Evoked Slow-Activity After tDCS in Disorders of Consciousness - Mensen, Armand; Bodart, Olivier; Thibaut, Aurore; Wannez, Sarah; Annen, Jitka; Laureys, Steven; Gosseries, Olivia (Frontiers in Systems Neuroscience, 2020)
Due to life-saving medical advances, the diagnosis and treatment of disorders of consciousness (DOC) has become a more commonly occuring clinical issue. One recently developed intervention option has been non-invasive transcranial direct current stimulation. This dichotomy of patient responders may be better understood by investigating the mechanism behind the tDCS intervention. The combination of transcranial magnetic stimulation and electroencephalography (TMS-EEG) has been a important diagnostic tool in DOC patients. We therefore examined the neural response using TMS-EEG both before and after tDCS in 7 DOC patients (4 diagnosed as in a minimally conscious state and 3 with unresponsive wakefulness syndrome). tDCS was applied over the dorsolateral prefrontal cortex while TMS pulses were applied to the premotor cortex. Analysis focused on two key measures of bistability in the TMS-EEG response: slow wave activity, and high-frequency suppression. None of the seven patients showed a relevant behavioural change after tDCS. We did however find that the overall evoked slow activity was reduced following tDCS intervention. We also found a positive correlation between the strength of the slow activity and the amount of high-frequency suppression. However, there was no significant pre-post tDCS difference in high-frequencies. In the resting state EEG, we observed that both the incidence of slow waves and the positive slope of the wave were affected by tDCS. Taken together, these results suggest that the tDCS intervention can reduce the slow wave activity component of bistability but this may not directly affect high-frequency activity. We hypothesise that while reduced slow activity may be necessary for recovery of neural function, especially consciousness, this alone is insufficient.